ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI MINAT MELANJUTKAN PENDIDIKAN KE PERGURUAN TINGGI PADA SISWA SMA DI KECAMATAN PULAU MERBAU KABUPATEN KEPULAUAN MERANTI - Rika '; Gimin '; Supentri ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This research is based on the low interest of high school graduates in Pulau Merbau sub-district to continue their study to university. Students' interest to continue their education to university is less than 50% of the number of students who graduate each year. The formulation of the problem in this research is how is the interest of high school students in Pulau Merbau District to continue their education to university and the factors that affect it. The purpose of this study is to determine the interest and factors that influence the interest of continuing education to university high school students in the district of Pulau Merbau. This research method is descriptive quantitative. The data were analyzed by using multiple linear regression. The results showed that the interest of continuing education to college in high school students in Pulau Merbau District is high upwards with 88,3% contribution. As for the factors that influence the interest of continuing education to university is the establishment of a person 1.070, the ideals 1.109, talents 1.006, family environment 0.272, school environment 0.345, community environment (-0.345), peer environment 0.135 and the socioeconomic parent 0.009. Thus the hypothesis stating "There is an influence between the interest of continuing education to college and the factors that influence it" is accepted. This is evidenced by multiple linear regression tests between variables X1, X2, X3, X4, X5, X6, X7, X8 and Y. Figures 11.381 and Ftable 2.12. Obtained from the study of Ftable distribution list with N = 60, at 5% significant level, thus can be known Fcount> Ftable or 11.381> 2.12 then H0 is rejected, so hypothesis in this research accepted.Keywords: Interest Continuing Education, Influencing Factors